1989
DOI: 10.1128/aac.33.9.1419
|View full text |Cite
|
Sign up to set email alerts
|

New directions for macrolide antibiotics: pharmacokinetics and clinical efficacy

Abstract: Erythromycin and related macrolide antibiotics have recently enjoyed a resurgence of clinical interest. This is a result of activity against organisms which are becoming more prevalent, particularly in immunocompromised hosts and, in addition, better understanding of the unique tissue penetration properties and potential immunomodulating properties of macrolides. Other features of clinical interest possessed by certain of the newer macrolides include the potential for once-daily dosing, resistance to acid degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 22 publications
1
73
0
1
Order By: Relevance
“…Expansion of the spectrum of the new macrolides offers an advantage over erythromycin.l29 l3 The pharmacokinetics of the new macrolides are characterised by improved oral bioavailability, increased tissue penetration and persistence, and longer clearance times compared with those of erythr~mycin.'~. 36 The frequency of adverse effects of erythromycin, such as dose-related epigastric distress, may be reduced with the new macrolides.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of the spectrum of the new macrolides offers an advantage over erythromycin.l29 l3 The pharmacokinetics of the new macrolides are characterised by improved oral bioavailability, increased tissue penetration and persistence, and longer clearance times compared with those of erythr~mycin.'~. 36 The frequency of adverse effects of erythromycin, such as dose-related epigastric distress, may be reduced with the new macrolides.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the reasons are its rapid acid degradation (6, 10) and relatively low plasmatic levels (6,11). Thus, the in vitro activities of the parent drug erythromycin are highly pH dependent, with activity decreasing with lower pHs.…”
mentioning
confidence: 99%
“…Unlike erythromycin, which is usually administered four times a day due to its serum halflife of approximately two hours, azithromycin has a serum half-life of between 2.0 to 2.5 days and has high tissue bioavailability (tissue half-life 57 hours), its level in tissues being approximately 10-fold greater than those in serum. 4,[21][22][23][24][25][26] These features imply that the dosing period for this drug could effectively be reduced while still achieving high concentrations at the site of infection. In this context, Stamm 26 recently reported that a single one gram oral dose of azithromycin was as effective as a standard seven day twice daily regimen of doxycycline and more effective than seven days of ciprofloxacin in eradicating uncomplicated chlamydial genital infections.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Azithromycin is one such drug with excellent in vitro activity against a wide spectrum of bacteria that includes many aerobic and anaerobic gram positive species and inhibits a number of clinically important intracellular pathogens like S. typhi, Chlamydia, Mycoplasma and Legionella. [2][3][4][17][18][19][20] We found that azithromycin was two to eight times less active than erythromycin against our isolates of staphylococci and streptococci, but more potent against H. influenzae and S. typhi. In addition to in vitro antibacterial activity, the pharmacokinetic properties are important factors in the therapeutic value of a chemotherapeutic agent.…”
Section: Discussionmentioning
confidence: 99%